Avaliação do programa de controle de infecção hospitalar em hospitais no município de Teresina-PI - Lima, Lucimá Alves Pereira (2011)
The control of hospital infection (HI) was, over the years, evolving and showing like a phenomenon that is not restricted to the hospital, but also to all health care establishments, which develop actions considered risk for the onset of infection. For the control of hospital infection to be carried out systematically by all who participate directly or indirectly in the process, and to meet the needs of each service, the existence of a Control Program of HI (CPHI) has the role of organizing this systematic and can act as an important tool of quality, because it allows the planning and execution of control actions in terms of HI. To evaluate the performance of the Program for Infection Control in hospitals in the city of Teresina, based on indicators validated nationally. It’s about a multiple case, descriptive, evaluative epidemiological study, conducted in 10 hospitals agreed formally to participate in this study. The variables studied relate to the structure and process. With regard to the structure were evaluated physical space, material, human resources and regulations. On the process, were evaluated operational practices that involve the activities of epidemiological surveillance as well as teaching and research. Data collection was performed with form closed questions, documents evaluation and interviews. The study population consisted of nurse members of HICCs of each hospital. In assessing the operation adequacy degree of the HICCs in the studied hospitals, was established scoring system, classifying them into very adequate, adequate, inadequate and very inadequate. The results showed that two hospitals stood out, where one presented a very adequate final score and the other, very inadequate. The latter has no active HICC. It was observed that in relation to the physical structure and material, six HICCs had very appropriate feature, two inadequate and one, very inadequate. As for human resources two HICCs scored very adequate for meeting the legal requirements in full, six inadequate and one adequate. With regard to operational practices, the type II, only one hospital had very adequate score (100%), while five had percentages between 69 - 84%, being considered as adequate in this regard. As for the operational practices III, that correspond to teaching and research, we note that only two scored very adequate, also two had appropriate scores and the others were considered inadequate and very inadequate. Therefore, the data obtained indicate the need for interest and support from managers, the organization of health professionals involved in changing the direction in reference to professional competence, making investments in scientific knowledge, development of technical skills, being it representing the organization or team.